Expanding the role of HsfA9 in cold adaptation: the bermudagrass CdHsfA9 confers cold tolerance in Arabidopsis via a novel regulatory module - Gan, Lu; Wang, Jiayu; Yan, Xuebing (Frontiers in Plant Science, 2025)
Low-temperature stress limits the growth and geographical distribution of bermudagrass (Cynodon dactylon (L.) Pers.), an important warm-season grass worldwide. While heat shock transcription factors (Hsfs) are well known for modulating heat stress responses, their functions in cold adaption remain poorly characterized. In this study, we identified and functionally characterized CdHsfA9, a novel Hsf gene isolated from bermudagrass, which localizes to the nucleus. Phylogenetic analysis revealed that CdHsfA9 clusters closely with HsfA9 orthologs from cereal plants and Arabidopsis AtHsfA8. Expression profiling indicated rapid upregulation under cold stress, with transcript abundance higher in leaves than in roots. Heterologous overexpression of CdHsfA9 in Arabidopsis promoted IAA content and enhanced cold tolerance, as evidenced by increased chlorophyll content, reduced leaf discoloration, and MDA accumulation in transgenic lines compared to mutants and wild-type plants under cold conditions. Transcription factor - centered yeast one-hybrid (TF-Y1H) assay identified 39 motifs bound by CdHsfA9, with target genes enriched in the metabolic and signal transduction pathways. Among these targets was serine/threonine-protein kinase D6PK-like, a key regulator in phosphorylation-related signaling. This direct binding of CdHsfA9 to the D6PKL promoter was confirmed by dual luciferase reporter assays in tobacco and ChIP-qPCR in Arabidopsis. Our findings extend the functional scope of HsfA9 beyond heat stress to include low-temperature adaptation and elucidate a broader stress regulatory network involving the CdHsfA9-HSEmotif-D6PKL module and its crosstalk with auxin. This study provides valuable genetic resources and theoretical foundations for improving cold resistance in forage grasses via molecular breeding.